2004
DOI: 10.1381/096089204323093354
|View full text |Cite
|
Sign up to set email alerts
|

Unfractionated Heparin Infusion for Thromboprophylaxis in Highest Risk Gastric Bypass Surgery

Abstract: For highest risk gastric bypass patients, an UFH prophylactic continuous infusion protocol was effective in preventing postoperative thromboembolic events. Hemorrhagic complications were easily managed and did not result in long-term sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 2 publications
0
17
0
1
Order By: Relevance
“…Although the choice of prophylactic dose used in our study was arbitrary and not based on patient's weight or anti-factor-Xa activity it appears to be safe and effective. In contrast, previous studies that used an in-hospital-only VTE prevention protocol based on anti-factor-Xa activity not only still reported a PE rate of 0.4%, but also observed a frequency of perioperative hemorrhagic complications as high as 10.5% [24,25].…”
Section: Discussionmentioning
confidence: 72%
“…Although the choice of prophylactic dose used in our study was arbitrary and not based on patient's weight or anti-factor-Xa activity it appears to be safe and effective. In contrast, previous studies that used an in-hospital-only VTE prevention protocol based on anti-factor-Xa activity not only still reported a PE rate of 0.4%, but also observed a frequency of perioperative hemorrhagic complications as high as 10.5% [24,25].…”
Section: Discussionmentioning
confidence: 72%
“…The widespread use of DVT prophylaxis and the increased frequency of laparoscopic gastric bypass have not decreased the rate of PE. The inadequacy of non-weight-based regiments of heparin and LMWH might have contributed to this limited success [1,4,6,9,[17][18][19]38]. Our patients were given 40 mg of LMWH twice daily for 2 weeks, rather than the standard 40 mg once-daily dose [16,18,38].…”
Section: Discussionmentioning
confidence: 99%
“…It would seem logical that a higher dose of anticoagulant would lead to lower PE rates, despite a lack of conclusive evidence supporting this idea. Several studies have demonstrated that the increased risks of bleeding from weight-based heparin and LMWH regimens are minimal [17,18,38]. Given the low risk and potential for benefit, we have chosen to use a greater than standard dose of LMWH.…”
Section: Discussionmentioning
confidence: 99%
“…Derived from this, there is a risk of overdosage in obese patients if a body-weight-adapted dosage is chosen [35]. Therefore, monitoring of Factor Xa is recommended for heparin administration in high-risk patients [36].…”
Section: Postoperative Prophylaxismentioning
confidence: 99%